Etika Dalam Menggunakan Media Sosial Pada Film Budi Pekerti - Nurul Hidayah Siregar; Ambar Sari Dewi (Laboratorium Sosiologi, Program Studi Sosiologi, Fakultas Ilmu Sosial, Universitas Nahdlatul Ulama Indonesia (UNUSIA) Jakarta, 2024)
Social media has become one of the most widely used online platforms by the public today. Its usage is no longer limited to teenagers but has extended to older adults as well. The widespread adoption of social media has led to significant changes in culture, mindset, and behavior within society. The aim of this study is to examine ethical behavior in the use of social media and to identify the impacts of its usage. This research employs a qualitative method by analyzing ethical considerations in social media practices through the lens of the film Budi Pekerti. The study adopts a critical paradigm, which serves as an analytical framework to assess, reflect on, and interpret a particular reality. The findings suggest that in Budi Pekerti, the case involving a school counselor (BK teacher) illustrates how a viral video can have profound personal and social consequences. This underscores the potential harm that social media can cause to individuals, highlighting the importance of ethical conduct in online interactions. Consequently, it is crucial for users to engage responsibly on social media and to refrain from hastily spreading unverified or misleading content.